2010
DOI: 10.1002/ejoc.201001083
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Triflate Catalyzed Intermolecular Aromatic Substitution of N,N‐Disubstituted Anilines with Diazo Esters

Abstract: The intermolecular aromatic substitution of N,N‐disubstituted anilines with diazo esters is achieved under mild conditions in the presence of a catalytic amount of copper(II) triflate (up to 89 % yield). The scope and limitations regarding substrates, diazo esters, and ligands in this reaction are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…This result clearly indicated an orthogonal reactivity of the gold catalyst compared to a dirhodium catalyst, which exclusively promoted the benzylic CÀH insertion without the occurrence of electrophilic aromatic substitution. [12] Scheme 1. Reactivity of gold-carbenoids: carbene versus carbocation.…”
mentioning
confidence: 99%
“…This result clearly indicated an orthogonal reactivity of the gold catalyst compared to a dirhodium catalyst, which exclusively promoted the benzylic CÀH insertion without the occurrence of electrophilic aromatic substitution. [12] Scheme 1. Reactivity of gold-carbenoids: carbene versus carbocation.…”
mentioning
confidence: 99%
“…Indeed, it was observed that a reaction involving indole, N-methylaniline, and 1a resulted in the unsymmetrical diaryl product 7, albeit in low yield. We investigated a few additional precursors and found that, while N-methylaniline and indoline afforded diarylated products in low yields (compounds 7,8,and 9;Scheme 2a),. Employing pyrrole in place of indole also did not lead to the desired product, indicating another limitation of this protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9 It was found that free anilines reacted via the para position to afford the unsymmetrical diarylacetates in generally high yields (52−86%). 10 Gratifyingly, N-benzylaniline provided the product in good yield, thereby overcoming the limitation of the direct protocol in Scheme 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The groups of Fox [4] and Wang [5] have reported ortho-selective C À H functionalization of heterocycles by using diazoacetates. In addition, other directing groups, such as purines, [6] azacycles, [7] disubstituted anilines, [8] and phenols, [9] have been utilized in metallocarbene CÀH alkylation reactions. Collectively, these directing groups limit the synthetic applicability of metallocarbene C À H alkylation reactions.Recently, Suero and co-workers reported the synthesis of aryl diazoacetate derivatives under photoredox conditions.…”
mentioning
confidence: 99%